Integrating research into undergraduate medical education curriculum: A 20-year experience from a medical school in coastal South India - Bhaskaran Unnikrishnan; T Rekha; Animesh Jain; Prasanna Mithra; Nithin Kumar; Ramesh Holla (Indian Journal of Community Medicine, 2022)
Research is the key to advancement in medical science. Medical school can nurture the skill of research right from the under graduation. Research forms an integral part of the medical curriculum in western countries. We attempted the same in our medical school in India. We developed a structured research methodology program, which was implemented in the undergraduate (UG) curriculum in two phases. Phase I focuses on research methodology and Phase II on manuscript writing. With the implementation of a competency-based medical education curriculum (CBME), we have extended the research methodology program with manuscript writing and introduction to systematic reviews, which is being offered as electives to UG medical students in the third professional year. Our experience in training students at an UG level has been immensely satisfying. We hope that this article will help other medical schools to adopt a similar method of training UG medical students in research methodology and scientific medical writing.